2015
DOI: 10.4238/2015.july.28.22
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interleukin-17 gene polymorphisms on the development of pulmonary tuberculosis

Abstract: ABSTRACT. We conducted a case-control study in a Chinese population to examine the correlations between interleukin (IL)-17 gene polymorphisms and tuberculosis (TB) development. The study population included 336 TB subjects and 351 control subjects who were enrolled between June 2012 and June 2014. Genotyping analyses of IL-17A rs2275913 and rs3748067 and IL-17F rs763780 were analyzed using polymerase chain reaction-restriction fragment length of polymorphism. The genotype distributions of IL-17 rs2275913 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 18 publications
1
35
0
2
Order By: Relevance
“…A possible cause of the discrepancies between those previous results and our present data might be related to ethnic differences. Nevertheless, another study in China demonstrated a relationship between the G allele and the GG genotype with resistance to tuberculosis disease13. However, the TB population studied did not show HW equilibrium.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…A possible cause of the discrepancies between those previous results and our present data might be related to ethnic differences. Nevertheless, another study in China demonstrated a relationship between the G allele and the GG genotype with resistance to tuberculosis disease13. However, the TB population studied did not show HW equilibrium.…”
Section: Discussionmentioning
confidence: 80%
“…In order to find an association with resistance/susceptibility to tuberculosis, several studies investigated the rs2275913 SNP in ethnically different populations910134142. In a Croatian41 and a Chinese42 populations, no association between the SNP and tuberculosis were detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Milano et al demonstrated that the A allele of IL17A (rs2275913) occurred more frequently in a control group than in patients with pulmonary tuberculosis and suggested that A or G allele in this position are associated with susceptibility to TB . Shi and Zhang concluded that the AA and GA + AA genotypes of rs2275913 are associated with increased risk of pulmonary tuberculosis . Ocejo‐Ocejo‐Vinyals et al demonstrated a correlation between IL‐17A rs2275913–152G allele and GG genotype and pulmonary tuberculosis and that (1s434666) serum IL‐17 titers were higher in patients than in controls .…”
Section: Discussionmentioning
confidence: 99%